2019
DOI: 10.1002/er.4440
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the methanol reforming process: Comparison of fuels, catalysts, reformers, and systems

Abstract: Summary One of the main challenges facing power generation by fuel cells involves the difficulties related to hydrogen storage. Several methods have been suggested and studied by researchers to overcome this problem. Among these methods, using fuel reformers as a component of the fuel cell system is a practical and promising alternative to hydrogen storage. Among many hydrogen carrier fuels used in reformers, methanol is one of the most attractive ones because of its distinctive properties. To design and impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(35 citation statements)
references
References 149 publications
(212 reference statements)
0
35
0
Order By: Relevance
“…[ 1–5 ] Currently, Hydrogen is mainly extracted from the reforming of traditional hydrocarbons such as diesel, methane and methanol, and the coal gasification process. [ 6–9 ] However, among those processes, massive environment‐unfriendly by‐products (e.g., CO, CO 2 ) are usually generated together with hydrogen production. Electrochemical hydrogen evolution reaction (HER) has been attracted more and more attention recently since it is considered as one of the greenest technologies to produce hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–5 ] Currently, Hydrogen is mainly extracted from the reforming of traditional hydrocarbons such as diesel, methane and methanol, and the coal gasification process. [ 6–9 ] However, among those processes, massive environment‐unfriendly by‐products (e.g., CO, CO 2 ) are usually generated together with hydrogen production. Electrochemical hydrogen evolution reaction (HER) has been attracted more and more attention recently since it is considered as one of the greenest technologies to produce hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Fuel cell is an attractive environmentally friendly energy conversion technology, but its application is very limited due to the difficulties associated with the transportation and storage of hydrogen [1][2][3]. A promising route for the broad adoption of fuel cells is through the so-called onboard fuel cell technology where H 2 is obtained via real-time steam reforming of hydrocarbon, such as methanol, which is liquid at room temperature and normal pressure [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Cu is the most commonly used commercial catalyst for the methanol steam reforming (MSR), CH 3 OH + H 2 O CO 2 + 3H 2 . However, Cu-catalyst suffers from some serious drawbacks such as pyrophoricity and catalyst sintering [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of the hydrogen production methods, including the environmental and economic impacts, is discussed in Acar and Dincer . More specially, a review on hydrogen production from methanol reforming can be found in Herdem et al…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of the hydrogen production methods, including the environmental and economic impacts, is discussed in Acar and Dincer. 1 More specially, a review on hydrogen production from methanol reforming can be found in Herdem et al 2 The reaction between Al and H 2 O is slow at low temperatures due to the coherent alumina (Al 2 O 3 ) passivation layer around the Al core that prevents its oxidation. Water must hydrate the Al 2 O 3 layer in order to break the Al─O bonds.…”
Section: Introductionmentioning
confidence: 99%